Modern biodegradable materials with accelerated degradation for dairy and food products (subject review) - D. M. Myalenko (Пищевые системы, 2023)
Products of the polymer industry, the lion's share of which is food packaging, create a significant threat to the environment, which requires a search for the most effective and functional solutions to this problem. Every year, the production of polymer packaging is growing by an average of 10-12%, and last year, due to the worldwide spread of SARS-CoV-2 (COVID-19) and its strains, the increase was more than 20%. A solution to the environmental problem is possible using the main basic approaches: disposal and recycling of waste, which will give the possibility of the “second life” to already used polymers; development and creation of new biodegradable materials capable of degrading completely under the influence of external factors into relatively safer substances. However, it should be noted that the first method has a number of significant drawbacks associated with the difficulty in controlling the amount of recycling processes carried out, which can potentially lead to an increase in migration processes from polymeric materials. The second way to solve the environmental problem of packaging disposal and recycling is the direction associated with the creation of polymeric materials with the replacement of part of the traditional commercial synthetic bases with organic and inorganic fillers in various concentrations. However, the most promising way to handle packaging waste, in our opinion, is the development of technologies aimed at creating fully biodegradable materials with a regulated service life, which, after their life cycle, are disposed of in a short time without harming the environment. This review is devoted to the analysis of the market of modern biodegradable materials and methods for obtaining degradable compositions that can become a significant alternative to traditional plastics.